Anxiety and depression in psychosis: a systematic review of associations with positive psychotic symptoms. (4th February 2013) - Hartley, S.; Barrowclough, C.; Haddock, G.
<x xml:space="preserve">Abstract</x> Objective This review explores the influence of anxiety and depression on the experience of positive psychotic symptoms, and investigates the possibility of a causal role for anxiety and depression in the emergence and persistence of psychosis. Method A systematic literature search was undertaken, producing a number of papers which comment on the links between anxiety and depression, and the experience of delusions and hallucinations. In addition, evidence which could contribute to our understanding of the causal role of anxiety and depression was highlighted. Results The findings show that both anxiety and depression are associated in meaningful ways with the severity of delusions and hallucinations, the distress they elicit and their content. However, the cross‐sectional nature of the majority of studies and the focus on certain symptom subtypes tempers the validity of the findings. Data from non‐clinical samples, studies which track the longitudinal course of psychosis and those which examine the impact of anxiety and depression on the prognosis for people experiencing psychosis, offer some support for the possibility of an influential role for anxiety and depression. Conclusion We conclude that anxiety and depression are related to psychotic symptom severity, distress and content and are also linked with sub‐clinical experiences, symptom development, prognosis and relapse. These links may imply that anxiety and depression could be targets for therapeutic intervention. The article concludes with suggestions for further research, highlighting avenues which may circumvent the limitations of the body of work as it stands.